2012
DOI: 10.1002/ardp.201100428
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Preliminary Pharmacological Investigation of New N‐Substituted‐N‐[ω‐(ω‐phenoxy‐alkylpiperazin‐1‐yl)alkyl]guanidines as Non‐Imidazole Histamine H3 Antagonists

Abstract: Novel, potent non-imidazole histamine H(3) receptor antagonists were prepared. Detailed structure-activity studies revealed that N-(4-trifluoromethylbenzyl)-N-[4-(7-phenoxyheptylpiperazin-1-yl)butyl]guanidine (pA(2)  = 8.49 ± 0.05), 1h, and N-(4-nitrobenzyl)-N-[4-(7-phenoxyheptylpiperazin-1-yl)butyl]guanidine (pA(2)  = 8.43 ± 0.05), 1l, exhibit high affinity for the H(3) histamine receptor. The most potent antagonists in this series, 1e, 1h, and 1l, were also in vitro tested as H(1) receptor antagonists, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Previously, our laboratory has described several non-imidazole piperazine- [ 28 , 29 ] and 4-hydroxypiperidine-based histamine H 3 antagonists with a moderate to pronounced affinity for the receptor [ 30 , 31 ]. The structure–activity relationship (SAR) of 4-hydroxypiperidines series showed that the most potent compounds, under in vitro screening conditions, were the benzofuranylpiperidinyloxy 1a ( ADS-003 ) (pA 2 = 8.47; Figure 1 ) [ 31 ] (for reference, thioperamide pA 2 = 8.67) and benzyl 1d (pA 2 = 7.79; Figure 1 ) derivatives [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our laboratory has described several non-imidazole piperazine- [ 28 , 29 ] and 4-hydroxypiperidine-based histamine H 3 antagonists with a moderate to pronounced affinity for the receptor [ 30 , 31 ]. The structure–activity relationship (SAR) of 4-hydroxypiperidines series showed that the most potent compounds, under in vitro screening conditions, were the benzofuranylpiperidinyloxy 1a ( ADS-003 ) (pA 2 = 8.47; Figure 1 ) [ 31 ] (for reference, thioperamide pA 2 = 8.67) and benzyl 1d (pA 2 = 7.79; Figure 1 ) derivatives [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds based on 1-[4-(piperazin-1-yl)but-1-yl]guanidine proved to be key to maintaining a high affinity at the histamine H 3 R. Based on previously obtained data of the guanidine series, two representative of the lead compounds, that is, ADS1017 and ADS1020 , were selected for further structural optimization. 31 , 32 In this paper, we have focused on the synthesis and pharmacological evaluation of a guanidine series where a flexible alkyl chain consisting of seven methylene groups, present in the lead compounds, is replaced by 1,4-cyclohexylene or p -phenylene group connected directly or by a methylene group to piperazine and phenoxy moieties. Additionally, for derivatives bearing a 1,4-disubstituted cyclohexylene group, the ( E ) and ( Z ) isomers were separated and pharmacologically tested independently ( Chart 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…N-Benzyl-4-(4-(7-phenoxyheptyl)piperazin-1-yl)butan-1-amine was prepared according to Staszewski and Walczyński. 29…”
Section: Methodsmentioning
confidence: 99%
“…28 Previously, we have reported the synthesis and preliminary pharmacological in vitro characterization of a series of potent histamine H 3 receptor non-imidazole antagonists belonging to the class of 1-substituted-1-{ω-[4-(ω-phenoxyalkyl)piperazin-1-yl]alkyl}guanidines. 29 The prominent members of this family are compounds carrying electron-withdrawing substituents in position 1 of the guanidine moiety or a chlorine atom at position 4 in the benzene ring, 1a (ADS-1024; pA 2 = 8.43), 1b (ADS-1020; pA 2 = 8.49), 1d, (ADS-1022; pA 2 = 7.80), respectively, and an unsubstituted benzyl residue 1c (ADS-1017; pA 2 = 8.21) ((Chart 1) for reference thioperamide (pA 2 = 8.72)). These compounds were also routinely screened for potency towards the histamine H 1 receptor and were found to possess weak but competitive H 1 antagonistic activity (pA 2 = 6.65, pA 2 = 6.46, pA 2 = 6.62, and pA 2 = 6.70, respectively) for this site in the functional assay on isolated tissue preparations of the guinea-pig ileum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation